2016
DOI: 10.1007/s10661-016-5387-z
|View full text |Cite
|
Sign up to set email alerts
|

Trace metal distributions in the sediments of the Little Akaki River, Addis Ababa, Ethiopia

Abstract: The levels and distribution of trace metals (Cr, Mn, Co, Ni, Cu, Zn, Cd and Pb) at eleven water and sediment stations on the Little Akaki River (LAR) in Addis Ababa, Ethiopia, were determined. The binding forms of the metals in various geochemical fractions of the sediments were also quantified. The molar ratio of the sum of the simultaneously extractable metals (∑SEM) and acid-volatile sulphide (AVS)-as a measure for predicting metal-induced toxicity-was estimated. LAR trace levels in water for Cu, Zn, and, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 31 publications
1
41
1
Order By: Relevance
“…For Ni and Cu, the PCA results suggested a behavior not dissimilar to that of Zn. Nickel was, in fact shown to be weakly bound to AVS (Peng et al ), and its distribution among binding phases was reported to be similar to that of Zn (Akele et al ). The PCA analysis confirmed the strong affinity of Cu for calcium carbonates, on whose surface sorption processes occur rapidly (Compton and Pritchard ).…”
Section: Discussionmentioning
confidence: 99%
“…For Ni and Cu, the PCA results suggested a behavior not dissimilar to that of Zn. Nickel was, in fact shown to be weakly bound to AVS (Peng et al ), and its distribution among binding phases was reported to be similar to that of Zn (Akele et al ). The PCA analysis confirmed the strong affinity of Cu for calcium carbonates, on whose surface sorption processes occur rapidly (Compton and Pritchard ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the trend of decreasing heavy metal concentration with increasing grain sizes was not straightforward (Figure 3 To account for the effect of OM and grain-size distributions in the content of heavy metals on sediments, it is important to normalize the variation based on these factors. Applying a normalization procedure as used in The Netherlands, comparing with a "standard sediment" with 25% fraction of < 63 µm and 10% OM content, yields results accounting for variation of heavy metals content owing to all existing ranges of grain-sizes and organic matter (Akele et al, 2016;Department of Soil Protection, 1994). This changes the estimated toxicity effect Preventing sustainable development: policy and capacity gaps for monitoring heavy metals in riverine water and sediments within an industrialising catchment in Ethiopia 57 (Table 3.4.…”
Section: Heavy Metals Quality Assessment In the Kombolcha Rivers And mentioning
confidence: 99%
“…Several studies report that the heavy metals concentrations in rivers, pose high risks in many sub-Saharan countries (see Table 3.6.). As the dilution capacity of the rivers to pollutants is diminishing in the face of intensifying consumption of river water for irrigation, storage and global climate change (Abdel-Satar et al, 2017), the deterioration of the rivers and sediment quality is widespread (Zinabu et al, 2017a;Akele et al, 2016). A critical assessment of heavy metals and their impact on river water quality are thus pressing needs.…”
Section: Efforts To Improve Monitoring Of Rivers' Water Quality In Etmentioning
confidence: 99%
See 2 more Smart Citations